2019
DOI: 10.1101/719815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cdc24, the source of active Cdc42, transiently interacts with septins to create a positive feedback between septin assembly and bud site formation in yeast cells

Abstract: Yeast cells select at the beginning of each cell cycle the position of their new bud. The recruitment of the septins to this prospective bud site (PBS) is one of the critical events in a complex assembly pathway that culminates in the outgrowth of a new daughter cell. The septin-rods follow hereby the high concentration of Cdc42 GTP that is generated by the focused location of its GEF Cdc24. We show that Cdc24 not only activates Cdc42 but temporarily interacts shortly before budding with Cdc11, the subunit tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…1). We have previously shown that Cdc11 interacts directly with Cdc24 and thus conclude that the Split-Ub-detected interaction between Cdc11 and Bem1 reflects the Bem1-Cdc24-Cdc11 complex (Chollet et al, 2019).…”
Section: Physical Dissection Of the Bem1 Interaction Networkmentioning
confidence: 83%
“…1). We have previously shown that Cdc11 interacts directly with Cdc24 and thus conclude that the Split-Ub-detected interaction between Cdc11 and Bem1 reflects the Bem1-Cdc24-Cdc11 complex (Chollet et al, 2019).…”
Section: Physical Dissection Of the Bem1 Interaction Networkmentioning
confidence: 83%